Attitude and Willingness of Practising Dairy Farmers sons to Work Permanently in Rural Area (Indian Journal of Extension Education, 2021)
The study on the attitude and willingness of sons of the practising dairy farmers towards permanently working in a rural area was carried on milk-producing districts of Anand and Kheda of Gujarat state with 200 sample size. The study reveals that the majority (96.50%) of the sons of practising dairy farmers had a favourable to highly favourable attitude towards permanently working in the rural area. It also concludes that the majority (80.50%) of the dairy farmers’ sons had poor overall willingness to stay physically to work in the rural area. The relationship of the attitude of young dairy sons of dairy farmers towards permanently working in the rural area was positively and significantly correlated with their age, marital status, scientific orientation, economic motivation and attitude towards farming, while it was negatively significant with the level of their father’s education. The willingness to work in the rural area was observed positively and significantly correlated with their level of father’s education, while it was negatively significant with their achievement motivation, self-confidence, scientific orientation, economic motivation and attitude towards farming.